Determinants of Trader Profits in Commodity Futures Markets - Dewally, Michaël; Ederington, Louis H.; Fernando, Chitru S. (Review of Financial Studies, 2013)
Using proprietary energy futures position data, we provide evidence that mean hedger profits are negative whereas speculator (especially hedge fund) profits are positive, that traders (whether speculators or hedgers) who hold net positions opposite in sign to likely hedgers in aggregate have higher profits than traders whose net positions align with likely hedgers, and that profits on long positions vary inversely with inventories and directly with price volatility. These findings are consistent with the risk premium, hedging pressure, and modern theory of storage hypotheses, respectively. Further, our findings suggest that commodity futures momentum may be due largely to hedging pressure.